A Spatial Economic Study of Rail Freight in the European Economic Area - Boldizsár, Adrienn; Mészáros, Ferenc (Promet - Traffic&Transportation, 2022)
The present study explores whether the European Union’s transport policy measures of the last decade have fulfilled the expectations, i.e. whether there has been a positive change in the field of rail freight transport in the region. Data on the volumes of freight transport in the recent period have been analysed with freight trans-port intensity as an indicator. The values have been then translated into a spatial econometric model, looking for spatiality in the European Economic Region, including countries such as Norway, Switzerland or even Russia, extending the scope of the study to 37 countries. It has been proven that there is a spatial correlation between rail freight transport performance and GDP in Europe, which has a positive effect on countries with high GDP and a negative effect on low GDP countries in terms of performance. There is a particularly high intensity of rail freight in the Baltic region, as well as in Ukraine and Russia. Furthermore, it can be stated that rail freight has not undergone any significant changes in the last 10 years.